Trace element analyses of melt inclusions as probes for the evolution of Bolivian tin porphyry deposits - Wallianos, Alexandros; Traxel, Kurt (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 1999)
Micron-sized melt inclusions (MI), trapped in host quartz crystals from rocks of magmatic systems, probe the evolution of ore deposits. PIXE in combination with NRA of light element concentrations provide a nearly complete database for geochemical characterisation. Tin deposits are usually associated with highly fractionated granitic magmatism. The tin porphyry deposits of Bolivia however have only a moderately fractionated bulk rock geochemistry. The investigation of MI revealed high degrees of fractionation with compositions similar to tin granites. It is supposed that the bulk rock geochemistry must be interpreted as the product of magma mixing. Unexposed granitic portions, represented by MI, provide magmatic vapour phases for hydrothermal alteration and mineralisation.